The Syntax of Question Formation in Ikpe - Abdullahi Babatunde Abdullahi (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
This study examines the Question formation in Ìkpè, one of the speech forms of Akoko spoken in Akoko South East Local Government Area of Ondo state, Nigeria. The study adopts Chomsky’s (1995) Minimalist Program for its analysis. The data for this research were gathered from informants whose age ranges between 50 and 70, these informants happen to be native speakers of the language and have a vast knowledge about the speech form. Findings reveal that question formation in the speech form is divided into two types; content question and polar question. It was discovered in the study that the speech form employed interrogative particles in forming a polar question in the speech form. Also, findings reveal that the process of content question involves the movement of the constituent from the extraction site to the landing site. This research serves as a part of the documentation of the syntax of Ìkpè.